Payment Choice, Image Motivation and Contributions to Charity - Adriaan R. Soetevent (Tinbergen Institute, 2009)
This paper examines the impact of payment choice on charitablegiving with a door-to-door fund-raising field experiment. Respondentscan donate cash only, use debit only, or have both options. Cash donations have lower visibility vis-a-vis solicitors than debit card donations. When debit replaces cash, participation drops by 87 percent.Conditional on participation, donors in the Debit-only treatment givemore than donors in Cash-only. In Cash&Debit, almost all donorsprefer cash; participation decreases compared to Cash-only. Physicalattractiveness of both female and male solicitors increases contributions. Solicitor self-confidence has a negative impact.
Keywords: C93; D64; H41; E42; 330; Payment choice; field experiment; image motivation; Fundraising; Altruismus; Privater Haushalt; Motivation; Reputation; Test